"Lights under a Bushel": a digest of highly cited papers from Construction Economics and Building (Construction Economics and Building, 2023)
There are times when a new editor ponders the iron triangle of quality submissions, readership, and citations, and how to improve them. It was during such a musing that a colleague from UTS/OJS pointed out that this journal had produced a suite of highly cited papers that was continuing to grow. They went on to illustrate the point with a list that stopped at a lower limit of 30 citations, observing that there was every likelihood that further good, recently published papers would continue this habit, given sufficient time (3-5 years). Grateful for their observations I scanned the list and was buoyed by the thoughts that these papers were a product of their time (i.e. highly relevant, reflecting topics of contemporary and ongoing concern), clearly well executed – conceptually and methodologically – and written in an engaging style. They were, and self-evidently continue to be read and cited, though the issue of growing our readership continues to be a challenge. In a world of burgeoning journal titles, many of which appear to be predatory in nature it can become necessary to remind readers of this tome that it is a valuable venue for the best of their research. The cost to publish and quality of the publication should be evident from its homepage, but that quality research within its pages can achieve high citation rates only becomes apparent once the reader searches for topics of interest to them. This digest is simply a reminder of what this journal – and those who support it with their time and effort – is all about. This selection of papers has been assembled from issues since the journal transferred online and adopted its current title. To reiterate, an arbitrary cut-off of 30 citations (Scopus) has been applied for the sake of brevity, though it is clear that there are more recent papers that are on target to match and exceed this citation score in the near future. Moreover, only bibliographic details and abstracts are included in this section; DOIs take the interested reader to the full paper. Please enjoy this retrospective.